2019
DOI: 10.1097/bot.0000000000001585
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nail Size, Insertion, and Δ Canal-Nail on the Development of a Nonunion After Intramedullary Nailing of Femoral Shaft Fractures

Abstract: Objective: To determine whether intramedullary nail (IMN) diameter, antegrade versus retrograde insertion, or the difference between the canal and IMN diameter affect femoral shaft fracture healing. Design: Retrospective analysis of a prospective database. Setting: Level One Regional Trauma Center. Patients/Participants: Seven hundred thirty-three femoral shaft f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…In a large retrospective analysis, Ma et al reported that nonunion was related to the use of an unreamed nail instead of a reamed nail 20 . However, in a more recent study, Serrano et al obtained similar union rates regardless of nail diameter or the difference between femoral canal diameter and nail diameter after reaming 21 . In our study, smaller nail size was a risk factor for non-union in all patients and in the closed reduction group.…”
Section: Subgroup Analysis To Identify the Risk Factors Of Non-unionmentioning
confidence: 84%
“…In a large retrospective analysis, Ma et al reported that nonunion was related to the use of an unreamed nail instead of a reamed nail 20 . However, in a more recent study, Serrano et al obtained similar union rates regardless of nail diameter or the difference between femoral canal diameter and nail diameter after reaming 21 . In our study, smaller nail size was a risk factor for non-union in all patients and in the closed reduction group.…”
Section: Subgroup Analysis To Identify the Risk Factors Of Non-unionmentioning
confidence: 84%
“…Filling of the IM nail in medullary canal was judged by the distance between inner cortical bone of the isthmic portion and IM nail in the AP and lateral plain radiographs. A distance of 2 mm or more between the inner cortical bone and the IM nail was considered insu cient lling 13 . The residual gap at the fracture site was de ned as a gap of ≥ 2 mm at each end of segment on the AP or lateral plain radiograph 14 .…”
Section: Assessment Of Outcomesmentioning
confidence: 99%
“…Currently, the treatment of choice for most of femoral shaft fractures is closed reamed locked intramedullary nailing and a high union rate with a low complication rate is generally predictable [ 2 ]. With such a technique, as high as the 94–98% union rate has been reported in the literature [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%